Inquiry into the Correlations between Sports Activity and Value Preference among Students in the Northern Great Plain Region as Regards the Role of Everyday Physical Education - Moravecz, Marianna (Central European Journal of Educational Research, 2022)
The vision of society can be influenced by the values young people hold regarding their way of life and physical well-being. Today, we are experiencing a crisis of these value preferences (Perényi, 2010). The aim of our study is to examine the effect of transferred sports values on the lifestyles of physically active and inactive students in light of the role of everyday physical education. In our research, 1521 students of the University of Debrecen and Nyíregyháza filled out the online questionnaire. Two-variable analyses and a multivariate principal component analysis were used, and the data were processed using SPSS. Regarding the relationship between sports activity and value orientation, the students included in the sample mostly focused on the “open” or post-material value dimension representing individual autonomy. This is in agreement with previous research data (Kovács, 2013; Perényi, 2010). Since this is a complex mechanism of action, we are unable to show causal relationships in our analysis. However, with regard to our research sample, it can be said that in the period since the introduction of everyday physical education, it has not yet had a demonstrable role in the physical activity and value system of students. Thus, promotion of an active lifestyle will, in the future, be critical in the lives of everyone. It will also prove essential in shaping the physical condition and mental well-being of the future’s society, not to mention it will help save the national economy. The first step in this process is the actual participating in physical education.